The Spatio-temporal Evolution of NDVI in the Three Gorges Reservoir Area Driven by the Synergistic Effect of two Factors over the Past 21 Years - QI Haimei; ZHENG Peilong; WANG Yunqi; WANG Jiani; LI Cheng; ZHANG Xiaoming (Shuitu Baochi Xuebao)
[Objective] To clarify the spatio-temporal characteristics of vegetation evolution in the Three Gorges Reservoir Area, and to quantitatively analyze the relationships between vegetation and key determinants, including climate, terrain, and human activities. [Methods] Based on Normalized Difference Vegetation Index (NDVI) data, a suite of analytical techniques was employed, including Theil-Sen Median Trend Analysis, the Mann-Kendall Test for significance, Hurst Exponent Analysis, and Geographic Detector Modeling, to investigate the spatio-temporal patterns and driving forces of NDVI within the Three Gorges Reservoir Area from the year 2000 to 2020. [Results] (1) The change of NDVI in the Three Gorges Reservoir Area showed an overall ascending trend from 2000 to 2020, with a mean annual rate of increase at 2.89×10-3/a, and the value of NDVI increased from the southwestern to the northeastern parts of the area. (2) Elevation, population density, and surface temperature are pivotal factors that significantly account for the variability observed in NDVI, with an explanatory power for each exceeding the threshold of 0.4. (3) Elevation and nocturnal illumination are the key interactive drivers of NDVI in the Three Gorges Reservoir Area, with a pronounced q value of 0.641. Their interplay showed a nonlinear or synergistic enhancement, and the integrated explanatory power of the two factors on NDVI changes is always greater than that of single factors. [Conclusion] The results of this study can offer a robust scientific support for the formulation of ecological and environmental conservation policies and for sustainable ecological development within the Three Gorges Reservoir Area.